Essential Oils from Clausena Species in China: Santalene Sesquiterpenes Resource and Toxicity against Liposcelis bostrychophila - Shan-Shan Guo; Yang Wang; Zhen-Yang Chen; Zhe Zhang; Ju-Qin Cao; Xue Pang; Zhu-Feng Geng; Shu-Shan Du (Journal of Chemistry)
To develop natural product resources from the Clausena genus (Rutaceae), the essential oils (EOs) from four Clausena plants (Clausena excavata, C. lansium, C. emarginata, and C. dunniana) were analyzed by GC-MS. Their lethal (contact toxicity) and sublethal effects (repellency) against Liposcelis bostrychophila (LB) adults were also evaluated. Santalene sesquiterpene was the precursor substance of santalol, a valuable perfumery. It was found that plenty of α-santalol (31.7%) and α-santalane (19.5%) contained in C. lansium from Guangxi Province and α-santalene (1.5%) existed in C. emarginata. Contact toxicity of the four EOs was observed, especially C. dunniana (LD50 = 37.26 µg/cm2). Santalol (LD50 = 30.26 µg/cm2) and estragole (LD50 = 30.22 µg/cm2) were the two most toxic compounds. In repellency assays, C. excavate, C. lansium, and C. emarginata exhibited repellent effect at the dose of 63.17 nL/cm2 2 h after exposure (percentage repellencies were 100%, 98%, and 96%, respectively). Four Clausena EOs and santalol had an excellent potential for application in the management of LB. Clausena plants could be further developed to find more resources of natural products.